Reconnecting marketing to markets - Araujo, Luis, 1970-; Finch, John.; Kjellberg, Hans. (Oxford : Oxford University Press, 2010)
This interdisciplinary book brings together theoretical and empirical contributions from marketing and economic sociologists to analyse and develop novel approaches to interpreting the relationship between marketing theory, marketing practices, and markets across a variety of market settings and countries.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Marketing -- Philosophy; Marketing -- Social aspects